Impact Study on Power Generation from Photovoltaic System due to Change in Local Irradiance and Temperature at Kathmandu Valley, Nepal - Shrestha, Manish; Bhattarai, Nawraj (Journal of the Institute of Engineering, 2017)
Solar Photovoltaic system has become popular among the renewable energy due to free availability and low maintenance costs. Economically, the decreasing cost from continuous development adds another motive for the use of photovoltaic system. There has been a continuous study regarding the estimation on output of the photovoltaic system, in normal operating conditions. The output is subject to variations due to various environmental factors. The aim of this study is to evaluate how Design of Experiments (DoE) Method is used to model the impact of meteorological data on the electric power generated by the photovoltaic system. In this paper, the simulation and experiment based analysis has been presented and the degree of impact of irradiance and temperature on the output power of the photovoltaic module has been illustrated. Journal of the Institute of Engineering, 2016, 12(1): 1-9